Using Tahsin Al-Qur’an Based on Self-Regulated Learning to Improve Students' Capabilities in Reading The Al-Qur’an - Suwarno; Muhammad Hatta; Mahdalena; Muhammad Almi Hidayat (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2023)
The purpose of this study was to determine the effectiveness of self-regulated learning-based tahsin Al-Qur'an in improving students' Al-Qur'an reading skills. The research method used was the quasi experimental method, the one group pretest-postest design. The experimental subjects in this study were 25 PGMI study program students in semester 3 of the 2022/2023 academic year. Research data were collected using tests in the form pre-test and post-test. Data analysis used statistical analysis with a paired sample t-test to determine the significance of the pre-test and post-test values. This research resulted in the finding that tahsin Al-Qur'an based on self-regulated learning could significantly improve students' Al-Qur'an reading ability. It could be seen from the paired sample t-test of 19.230 which was higher than the t-table of 2.064 (df 24) with a significant value of 0.000, which was lower than 0.05.